Factors impacting compliance with standard precautions in nursing, China - Luo, Yang (Int J Infect Dis, 2010)
OBJECTIVES: To evaluate registered nurse compliance with standard precautions and to analyze the factors that affect compliance. METHODS: Study data were collected over a 3-month period from June to September 2007. The survey research method was used. A total of 1500 randomly sampled registered nurses from 18 hospitals in Hunan, China completed self-report questionnaires. RESULTS: Of the 1500 nurses included in the study, 1444 returned valid self-report questionnaires. Compliance with standard precautions was found to be low in the surveyed nurses. With a maximum possible score of 80, the quartile range of the overall score for compliance for all nurses was 48.29 (upper quartile score 76.36, lower quartile score 28.07), which was occupied by 64.7% of the participants. The factors most affecting compliance were: standard precautions training (odds ratio (OR) 2.17, 95% confidence interval (CI) 1.85–2.55) and knowledge (OR 1.94, 95% CI 1.01–3.41), followed by hospital grade (OR 1.61, 95% CI 1.79–1.86), presence of sharps disposal box in the department (OR 1.43, 95% CI 1.10–3.41), general self-efficacy (OR 1.29, 95% CI 1.04–1.59), exposure experience (OR 0.69, 95% CI 0.56–0.85), and department in which the nurse worked (OR 1.24, 95% CI 1.05–1.46). CONCLUSIONS: The relevant authorities and hospital infection control department should pay more attention to nurse compliance with standard precautions. Standard precautions training should be strengthened and sufficient practical personal protection equipment provided in order to reduce hospital infections and protect the health of patients and medical staff.